Graduate Farmers’ Perception on the Accessibility of Online Information Provided by Agricultural Agencies - Kamaruddin, Norfaryanti (2007)
The modernisation of Malaysian agricultural sector has accelerate due to deliberate improvements in the delivery of critical agricultural support services, such as Research and Development (R&D), education and training, as well as technical and financial support. A number of government and private agencies have produced a significant number of research outputs, such as new technologies and processes, and agricultural knowledge as documented in research and academic journals, academic papers, and research reports. At the same time, rapid development in information and communication technology (ICT), which acts as an enabler in the development of the economy, has gained tremendous acceptance by the society in turning Malaysians into the so-called knowledge workers. Unfortunately, in the agricultural sector, in spite of all these development, the general users of agricultural knowledge, especially farmers, have difficulty in accessing knowledge through the use of technologies, which have been generated by various agricultural organisations. Therefore, the objectives of this study are (1) to evaluate the usability and usefulness of agriculture portals, (2) to determine the frequency of accessing agricultural knowledge through portals or websites and (3) to identify factors affecting the access to agricultural knowledge through these agriculture portals or websites. For the first objective, a panel of experts evaluate the relevant agriculture portals and websites. Whereas, for the second objective, the respondent were participants of the Agriculture Entrepreneurs Scheme for Graduates under Agriculture Bank of Malaysia. Primary data were collected using a mail survey and about 40% of the scheme participants responded. Factor Analysis and Multiple Regression Analysis (MRA) were used to achieve the second specific objective. The most frequently visited agriculture portals or websites are those of the Ministry of Agriculture, Agriculture Bank of Malaysia, and Department of Veterinary Services. The Factor Analysis identifies five important factors affecting the access to agricultural knowledge by the graduate agricultural entrepreneurs. The factors are; levels of agriculture knowledge, ICT skills, computer usability, complimentary sources of knowledge, and business knowledge. Based on the MRA the variables that significantly affect the frequency level of accessing agricultural knowledge includes ICT skills,business knowledge and the number of time succeeded in getting the information needed. Based on the findings, there is a need for R&D agencies to work closely with the farmers to produce relevant and useful research outputs. Subsequently, these new knowledge and technologies should be easily accessible through user-friendly portals; and at the same time, the agricultural entrepreneurs must equip themselves with ICT and other agriculture knowledge in order to reap the benefits of accessing and applying new knowledge and technologies generated by the agricultural organisations.